Способы определения состава бетона различных видов: [учеб. пособие для строит. специальностей вузов] / Ю. М. Баженов - Баженов Юрий Михайлович (Стройиздат, 1975)
Экземпляры: КХ (20120816) / Инвентарный номер: 607906 / Цена: 0.63 / Сис.шифр: 691 / Авт.знак: Б 16 / ГРНТИ: 67 / ББК: 38